2013
DOI: 10.29302/oeconomica.2013.15.1.3
|View full text |Cite
|
Sign up to set email alerts
|

"Fair Value Measurement Disclosures: Particularities In The Context Of Listed Companies And European Funding "

Abstract: In the last years and especially after the outbreak of the recent financial and economic crisis, fair value and implicitly fair value measurements for financial statements have been harshly criticized, mainly by the representatives of the companies activating in the financial sector. Therefore, the aim of this paper is to study the issue of disclosures on fair value measurements in the financial statements by firstly sketching a guide of best practices and further focusing on empirically documenting potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
5
0
5
Order By: Relevance
“…The findings are thus in line with the conclusions of Tsalavoutas (2011), which found, in a more crosssectional study on the subject, differences between the levels of disclosures for IAS 19, IAS 36, and IAS 37. It also corroborates, in another perspective, the divergences between the levels of disclosure identified and the different studies that used, individually, the same IAS and IFRS proposed in this study, namely for IFRS 13 (Kasyan et al, 2018;Matiş et al, 2013), IAS 19 (Street & Gray, 2002), IAS 36 (Glaum et al, 2013;Paugam et al, 2013), and IAS 37 (Alnaas & Rashid, 2019).…”
Section: Discussion Of Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The findings are thus in line with the conclusions of Tsalavoutas (2011), which found, in a more crosssectional study on the subject, differences between the levels of disclosures for IAS 19, IAS 36, and IAS 37. It also corroborates, in another perspective, the divergences between the levels of disclosure identified and the different studies that used, individually, the same IAS and IFRS proposed in this study, namely for IFRS 13 (Kasyan et al, 2018;Matiş et al, 2013), IAS 19 (Street & Gray, 2002), IAS 36 (Glaum et al, 2013;Paugam et al, 2013), and IAS 37 (Alnaas & Rashid, 2019).…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…Regarding size, the literature is identified in line with the initial propositions, with a predominance of investigations that find a positive association (Ali et al 2004;Alkababji, 2016;Alnaas & Rashid, 2019;Demir & Bahadir, 2014;Devalle & Rizzato, 2013;Guerreiro, 2006;Lopes & Rodrigues, 2007;Matiş et al, 2013;Oliveira & Lemes, 2011;Owusu-Ansah, 1998;Richardson & Welker, 2001;Santos et al, 2014;Singhvi & Desai, 1971;Street & Gray, 2002;Wallace & Naser,1995;Zarzeski, 1996). On profitability, there is research that found a positive relationship (Ali et al, 2004), but also the opposite (Wallace & Naser, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 77%
See 2 more Smart Citations
“…This line of research analyses whether IFRS 13 has improved previous fair value disclosures in financial statements, and whether companies are complying with IFRS 13 in this respect. Matis et al (2013) analyse diversity in fair value disclosures and its determinant factors. They use a sample of 20 companies listed on the London Stock Exchange and the Frankfurt Stock Exchange.…”
Section: Ifrs 13/asc 820 Disclosures Qualitymentioning
confidence: 99%